The benefits to be derived by the stockmen from the eradication of contagious diseases - Sullivan, Dan C. (My University, 1908)
Introduction: As an industry stock raising is classes as one of the highest. Since the beginning of man the horse, cow, and other domestic animals have been his companion, his beast of burden, have furnished material for his clothing, have served as his food; even back in Bible times we read of herds of cattle being raised and used by means of profit by the people.
Citation: Sullivan, Dan C. The benefits to be derived by the stockmen from the eradication of contagious diseases. Senior thesis, Kansas State Agricultural College, 1908.
Keywords: Stock; Cattle; Disease; Agriculture; Graduating theses; Senior theses; Theses